3(4x+9)=

Simple and best practice solution for 3(4x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+9)= equation:


Simplifying
3(4x + 9) = 0

Reorder the terms:
3(9 + 4x) = 0
(9 * 3 + 4x * 3) = 0
(27 + 12x) = 0

Solving
27 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 12x = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 12x = 0 + -27
12x = 0 + -27

Combine like terms: 0 + -27 = -27
12x = -27

Divide each side by '12'.
x = -2.25

Simplifying
x = -2.25

See similar equations:

| a+4=2a+20 | | v(t)=7+0.7t^2 | | 4(2b-14)=5b+1 | | 5(3x-2)-4(x+11)=7 | | (2x)^2/0.1-x | | -2x-8y=-6 | | -2(w+1)-(5w-9)=-8w | | s(2b-14)=5b+1 | | 90+9x+x^2=0 | | 9-9x=101-5x | | x/5+7=-1 | | 7x-56=16-2x | | -3.8=0.2-2y | | (3X)-4=7 | | N+3-c=b | | r^2-21=4r | | -2/3x-4=7 | | 3x=2x+24 | | 2(3n-3)=(8n+9)+8 | | 1/2x-2 | | x^2+3x-2.72=0 | | N=-3-c-b | | 3x-4=x-38 | | 4x+7=4(x-2) | | 5z-3=6+2zy | | -91+6x+x^2=0 | | 4x+9=7x-35 | | 4x+9=-7x-35 | | 5j+9=3d+3 | | 2(s+1.6)-5(2-5)=-1.9 | | 23-2x=7+2x | | z^2+(1+2i)+(1+7i)=0 |

Equations solver categories